Evaluation of detectability of differential type probe using directional eddy current for fibre waviness in CFRP. (14th September 2020) - Kosukegawa, Hiroyuki; Kiso, Yuta; Hashimoto, Mitsuo; Uchimoto, Tetsuya; Takagi, Toshiyuki
Abstract : This paper describes the detectability of eddy current testing (ECT) using directional eddy current for detection of in-plane fibre waviness in unidirectional carbon fibre reinforced plastic (CFRP) laminate. Three different types of probes, such as circular driving, symmetrical driving and uniform driving probe, were proposed, and the waviness angle was extracted from the contour map of the ECT signal by applying a Canny filter and a Hough transform. By comparing both the waviness angle estimated by ECT and that obtained by an X-ray CT image, the standard deviation (precision) and root mean square error (accuracy) were evaluated to discuss the detectability of these probes. The directional uniform driving probe shows the best detectability and can detect fibre waviness with a waviness angle of more than 2° in unidirectional CFRP. The probe shows a root mean square error of 1.90° and a standard deviation of 4.49° between the actual waviness angle and the angle estimated by ECT. This article is part of the theme issue 'Advanced electromagnetic non-destructive evaluation and smart monitoring'.